Analisis Kualitas Pelayanan pada Peserta BPJS Kesehatan Non BPJS Kesehatan Stabat, Langkat - Selvia Selvia; Fauzi Arif Lubis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
ABSTRACT.The public service center is a very important service and is a top priority for administrators to meet the needs of the community. Health is one of the first facilities for health BPJS participants that can be obtained at the Puskesmas or clinic. The services provided are very useful to help the community, including BPJS patients. So that the services provided to patients must be of quality according to the specified service standards. Conducting this research aims to identify and discuss services for BPJS Health and Non BPJS Health participants as well as supporting and inhibiting factors for services. The research method used is qualitative by understanding the research subject. data collection techniques by observing and studying the literature to collect theories, regulations and information obtained from books and documents in the form of journals. The results of the study stated that the quality of services provided to BPJS Health and Non BPJS Health patients at the Langkat BPJS office was good and in accordance with the needs of the community, namely responsiveness, assurance, and empathy. Factors supporting the service are the attitude of employees who are friendly as well as polite, clear and patient in conveying information and services, but there are still things that need to be improved, namely the lack of supporting facilities and infrastructure, such as loudspeakers, wifi networks and the incompatibility of the number of busy participants with the number of officers working or serve.Â Keywords: Quality, Service